11. EVALUATION OF TREATMENT OUTCOMES FOR NON-OPERATIVE MANAGEMENT OF BLUNT RENAL TRAUMA AT PEOPLE'S HOSPITAL 115 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the non-operative management outcomes of blunt renal trauma and associated factors at People's Hospital 115.Subjects and Methods: A combined retrospective and prospective cohort study. All cases of blunt renal trauma were treated at People's Hospital 115 from January 2021 to April 2025. The prospective phase was conducted from April 2024 to April 2025, while the retrospective phase spanned from January 2021 to March 2024.Results:The mean age of patients was 41.4 ± 17.2 years, with the 20–39 age group being the most affected (40%). Conservative management was the primary treatment modality, applied in 74% of cases, and mainly indicated for low- to moderate-grade injuries. JJ stent placement and angioembolization were performed in 18% and 8% of patients, respectively. Good treatment outcomes were achieved in 84% of patients, with no conversions to open surgery or in-hospital deaths. Complications occurred in only 4% of cases. A statistically significant association was found between treatment outcomes and both injury grade (p = 0.032) and treatment method (p = 0.029). Among patients with good outcomes, 61.9% had a hospital stay of 7 days or longer, while all patients with fair outcomes were hospitalized for 7 days or longer. The difference in hospital stay length between the two groups was statistically significant (p = 0.043).Conclusion:Non-operative management of blunt renal trauma, particularly in hemodynamically stable patients with low- to moderate-grade injuries, is effective and associated with favorable outcomes and low complication rates. The findings support a conservative-first approach, with selective use of JJ stents or angioembolization based on injury severity.
Keywords: Blunt renal trauma; Non-operative management; JJ stent; Angioembolization.